Kepemimpinan Perempuan dalam Human Service Organization (Studi di SBMI Wonosobo) - Azzhara, Ni Made Ray Rika (Neolectura, 2025)
The purpose of this study is to determine the leadership of women in migrant workers’ organizations in Serikat Buruh Migran Indonesia (SBMI) Wonosobo. The type of research used is qualitative research with observation and interview methods. The theory used is critical theory in organizational studies that focuses on gender equality in organizations. The results showed that women leaders are able to develop Human Service Organizations (HSO) with the women’s leadership strategy used, namely servant leadership. This leadership style prioritizes the common interests and aspirations of the people being led as well as an orientation to serve. Some characteristics of this leadership style include love, empowerment, vision, humility, and trust. This strategy is considered effective because it can develop organizations and realize gender equality.